Lean Service-inventory Management Integrated Model to Improve the Service Level in a Metalworking Company - Alfaro, F. G. (2022)
The importance of the metalworking sector in Peru is reflected in the high demand for machinery, equipment and structures in various economic sectors such as industry, construction, mining, transportation, among others. This makes it a generator of large productive links and employment. Today, the struggle to follow a quality standard that guarantees the production of these goods persists, as well as the effort to improve the customer's perception of the service offered. This study proposes an integrated model to increase the service level of a metalworking company through the use of Lean Service and Inventory Management tools. The results show a 10.13% increase in the service level, thanks to the implementation of engineering concepts such as 5s, Kaizen and Inventory Management.